SOCIOSYSTEM OF THE GLOBALIZATION OF HIGHER EDUCATION: TRENDS, CONSEQUENCES AND PROSPECTS - Zinchenko, Viktor V. (Educological discourse, 2015)
The article is devoted fundamental problems and values strategies of education in the river-bed of system approach. Such integration of knowledge and approaches should be carried out, first of all, by philosophy (focused on a context of social development by education philosophy – social philosophy of education) at level of ontologic and methodological representations and concepts.